Sosialisasi Ekonomi Kreatif di Desa Siharang Karang Kecamatan Padangsidimpuan Hutaimbaru - Silviana Batubara; Makhrani; Wisnu Yusditara (Jurnal Transformasi Pendidikan Indonesia, 2024)
The creative economy is an idea that is expected to provide added economic value. The creative economy is also an alternative solution to economic problems. The younger generation has a great opportunity to advance and improve the Indonesian economy. It is important to socialize the creative economy to the community so that local people, especially in Siharang Karang Village, Padangsidimpuan Hutaimabaru District, have a high desire to pursue a creative economy. Socialization is a process that helps people to learn and adapt to their way of life and how to think, in order to gain knowledge about the correct procedures for socializing in the community. The aim of this socialization is to develop understanding and development of abilities in the field of creative economy. This service activity was carried out for 3 (three) months with 3 (three) stages, namely preparation, implementation and evaluation. After the socialization was held, the community understood and developed capabilities in the field of creative economy in the community and were able to increase understanding and development of abilities regarding the role of the younger generation in the field of creative economy.